Cation distribution and magnetic properties of Zn-substituted CoCr2O4 nanoparticles - Jagadish Kumar G.; Banerjee A.; Sinha A.S.K.; Su Y.; Nemkovski K.; Rath C. (My University, 2025)
CoCr2O4 is a normal spinel where Co occupies the tetrahedral (A) site and Cr occupies the octahedral (B) site; it is important to examine the cation distribution and magnetic properties by substituting a non-magnetic ion like Zn. In this context, we have synthesized pure phase ZnxCo1-xCr2O4 (x = 0.05, 0.1) of crystallite size 10 nm through conventional co-precipitation technique. Fourier transform of Co, Zn, and Cr K-edge spectra obtained from extended X-ray absorption fine structure demonstrates that while Co and Zn prefer the A site, Cr strongly occupies the B site. The paramagnetic to long range ferrimagnetic transition, TC, decreases from 97 K in CoCr2O4 (bulk) to 87.4 K at x = 0.1 with an intermediate TC of 90 K at x = 0.05. The decrease in TC is ascribed to decrease in A-B exchange interaction confirming the preferential occupation of Zn2+ ions towards the A site. The spin-spiral transition, TS, decreases from 27 K in bulk (CoCr2O4) to 24 K at x = 0.1 followed by a spin lock-in transition, TL, observed at 10 K which remains unchanged with increase in Zn concentration. The diffuse neutron scattering in both compositions shows the evidence of long range spiral ordering in contrast to the simultaneous formation of long and short range order in single crystals of CoCr2O4. The decrease in maximum magnetization from 9 to 8 emu/g and an increase in coercivity from 3.2 to 5.2 kOe at 2 K with an increasing Zn concentration from 0.05 to 0.1 have been explained by considering the Yafet-Kittel model. © 2018 Author(s).